دور المراجعة البيئية في تقييم الأداء البيئي للمؤسسات الإقتصادية – دراسة حالة المؤسسة الوطنية للدهن - فرع سوق اهراس - للفترة ) 2019-2021 - سيف الإسلام عواينية; عبد الحميد ناصري (My University, 2022)
The study aimed to identify the role of environmental auditing in dividing the environmental performance of economic institutions, and the study was dropped on the National Oil Corporation - Souk Ahras Unit - for (2019 -2021). In order to answer the problem of the study, it was relied on the descriptive and analytical approach. The study concluded that the environmental audit is a tool for assessing the environmental performance of institutions and works to measure and improve it, which made it more than an inevitable necessity .The study also found the importance of adopting an environmental management system by the National Oil Corporation - Souk Ahras Unit - through waste management, ensuring occupational safety for the institution’s employees and trying to produce environmentally friendly products and preparing for obtaining ISO 14001 and 18001 certificates in the future. The study recommends the need to adopt a system Environmental management and carry out an environmental audit to assess its environmental performance. ........................................................ هدفت الدراسة إلى التعرف على دور المراجعة البيئية في تقييم الأداء البيئي للمؤسسات الإقتصادية و تم إسقاط الدراسة على المؤسسة الوطنية للدهن وحدة سوق أهراس للفترة ) 1919-2021(.و للإجابة على – - - إشكالية الدراسة تم الإعتماد على المنهج الوصفي و التحليلي. توصلت الدراسة إلى أن المراجعة البيئية تعتبر أداة لتقييم الأداء البيئي للمؤسسات و تعمل على قياسه و تحسينه ، الأمر الذي جعلها أكثر من ضرورة حتمية .كما توصلت الدراسة إلى أهمية تبني نظام الإدارة البيئية من قبل المؤسسة الوطنية للدهن وحدة سوق أهراس من خلال تسيير النفايات و تأمين السلامة المهنية للعاملين – - بالمؤسسة و محاولة إنتاج منتجات صديقة للبيئة و التحضير للحصول على شهادة الإيزو 14001و18001مستقبلا. لتوصي الدراسة بضرورة تبني نظام للإدارة البيئية و القيام بالمراجعة البيئية لتقييم أدائها البيئي.